PENGARUH PENGAWASAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PANEN PT XYZ - Iskandar, Iskandar (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
The purpose of this study was to determine the effect of supervision on the work productivity of PT XYZ's harvest employees. To achieve this goal, research was conducted using a sample of 62 people, using the census method. The data analysis method used simple linear regression. Based on the test results on the control variable (X) using the help of SPSS, the t-count is greater than the t-table (5.827 > 2.000). Thus, it can be concluded that the variable X or the supervision variable has a positive and significant influence on the work productivity of PT XYZ's harvest employees. Value (R2) = (0.601 X 0.601 = 0.361) or 36.1% then the percentage of the contribution or contribution of the supervision variable to the productivity variable is 0.361 or 36.1% while the remaining 63.9% is influenced by other variables that are ignored or not investigated in this research